Probiotic and genomic evaluation of Lactiplantibacillus plantarum T31 isolated from tempoyak in mung bean substrate - QONITA GINA FADHILAH; AUDREY ELIZABEHT; MELINDA FALENCIA; IMAN SANTOSO; ANDI EKO MARYANTO; NIARSI MERRY HEMELDA; MARDIASTUTI H. WAHID (Society for Indonesian Biodiversity, 2025)
Abstract. Fadhilah QG, Elizabeht A, Falencia M, Santoso I, Maryanto AE, Hemelda NM, Wahid MH. 2025. Probiotic and genomic evaluation of Lactiplantibacillus plantarum T31 isolated from tempoyak in mung bean substrate. Biodiversitas 26: 4435-4444. Traditional fermented foods in Indonesia contain diverse beneficial microorganisms, including Lactic Acid Bacteria (LAB), which play an important role. LAB T31 has been isolated from tempoyak and evaluated for probiotic characters. In this research, the isolate was evaluated as a potential probiotic in a mung bean substrate to develop a healthy fermented drink. The result showed that LAB T31 grew well on the mung bean substrate. The population increased from 107 CFU/mL to 109 CFU/mL after 24 hours of incubation. The viability results showed that the LAB T31 population remained 10? CFU/mL after 30 days at 10°C. Cell-free filtrate of fermented mung bean substrate showed antibacterial activity against the tested bacteria. The diameter of inhibition increases from 24 hours (15-17 mm) to 48 hours (16-18 mm) of incubation. Whole genome sequences (WGS) of the isolate were performed using DNBseq technology, and the re-identification using JspeciesWS and FastANI showed that the strain belonged to Lactiplantibacillus plantarum. Analysis of the antibacterial assay test result showed that the LAB T31 genome encoded an antimicrobial peptide known as plantaricin. The hydrophobicity and auto-aggregation reached 38.86% and 36.92%, respectively, after 24 hours of incubation. Functional annotation reported adhesin genes, and the isolate did not suggest hemolytic activity on blood agar. These results supported WGS analysis using KEGG since the reported genes are not related to hemolytic ability and virulence factors. Moreover, antimicrobial resistance analysis showed that the isolate had a vanY gene, with a similarity level of 33.33%. LAB T31 was a potential isolate as a probiotic agent in the mung bean substrate.